Ketamine suppresses hypoxia‐induced inflammatory responses in the late‐gestation ovine fetal kidney cortex - Chang, Eileen I. (J Physiol, 2015)
The fetus responds to decreases in arterial partial pressure of oxygen by redirecting the blood flow mainly to the brain and the heart, at a cost to other peripheral organs like the kidneys. Renal hypoxia and ischaemia stimulate inflammatory and apoptotic responses. Ketamine, an NMDA receptor antagonist, is able to reduce renal immune and inflammatory gene expressions stimulated by hypoxia. Ketamine may have therapeutic potential for protection against ischaemic renal damage in fetuses subjected to acute hypoxia.